Makna Welfare State Ditinjau dari Implementasi Pasal 34 Ayat (1) Undang-Undang Dasar 1945 - Afgha Okza Eriranda; Fajar Rahmad.S; Eny Kusdarini (Jurnal Hukum IUS QUIA IUSTUM, 2024)
Social welfare is a crucial element of a nation, which involves various aspects of life such as health, education, economy, environment, social, and politics that are included in the concept of welfare state. The implementation of Article 34 paragraph (1) of the 1945 Constitution in practice displays various obstacles faced by the government in actualising social welfare. This study indicates the significance of the welfare state as a critical review and evaluation and an effective scheme, so that it is used as an antidote by focusing on the constitutional mandate which is the basis for this research. This research uses a normative legal research study method with a conceptual approach and a regulatory approach. The results of this study highlight the significance of the welfare state in creating welfare according to the constitutional mandate that has been stated. Focusing on the concept of the welfare state, examining the active role of the state in ensuring a fair distribution of social welfare, and protecting human rights through social security. This reflects the commitment of the Indonesian government to fulfill the fundamental rights of its citizens, especially those who are still less fortunate. These actions reflect the dedication of the state to addressing social and economic disparities through various redistribution measures. The constitutional mandate emphasizes the central role of the welfare state in the layout of the national development of Indonesia. This comprehensive analysis is expected to provide significant contributions in improving the implementation of social welfare policies and achieving the constitutional goal of optimally caring for the less fortunates and neglected children.Keywords: Justice, Welfare, Welfare State. AbstrakKesejahteraan masyarakat adalah aspek penting dalam suatu negara, melibatkan berbagai aspek kehidupan seperti kesehatan, pendidikan, ekonomi, lingkungan, sosial, dan politik yang tercakup dalam konsep welfare state. Implementasi Pasal 34 ayat (1) Undang-Undang Dasar 1945 pada praktiknya, menunjukkan berbagai kendala yang dihadapi pemerintah dalam menciptakan kesejahteraan masyarakat. Kajian ini memperlihatkan kebermaknaan welfare state sebagai tinjauan dan evaluasi kritis serta skema efektif, sehingga dijadikan sebagai penawar dengan berfokus sesuai amanat konstitusi yang menjadi landasan pada penelitian ini. Riset ini mempergunakan metode kajian penelitian hukum normatif dengan pendekatan konseptual dan pendekatan perundang-undangan. Hasil penelitian ini menyoroti kebermaknaan welfare state dalam menciptakan kesejahteraan sesuai amanat konstitusi yang telah dicantumkan. Fokus pada konsep welfare state, mengkaji peran aktif negara dalam memastikan distribusi kesejahteraan sosial yang adil, serta melindungi hak asasi manusia melalui jaminan sosial. Hal ini mencerminkan komitmen pemerintah Indonesia untuk memenuhi hak-hak dasar warganya, khususnya mereka yang masih kurang beruntung. Tindakan tersebut mencerminkan dedikasi negara dalam menangani disparitas sosial dan ekonomi melalui langkah-langkah redistribusi yang beragam. Amanat konstitusi tersebut menegaskan peran sentral welfare state dalam pembangunan nasional Indonesia. Analisis komprehensif ini diharapkan memberikan kontribusi signifikan dalam memperbaiki implementasi kebijakan kesejahteraan sosial dan mencapai tujuan konstitusional untuk memelihara fakir miskin dan anak terlantar secara optimal.Kata Kunci: Keadilan, Kesejahteraan, Negara Kesejahteraan.